2020
DOI: 10.1097/nna.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Nurses' Perception of Workplace Violence Based on Specialty

Abstract: OBJECTIVE The aim of this study was to evaluate the impact of inpatient nursing specialties on the perceptions of workplace violence. BACKGROUND The association between nursing specialty and the perception of workplace violence has not been identified. METHODS An evaluation of inpatient nurses’ perceptions of workplace violence at a single health system was conducted using a modified Survey of Violence Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…This study found that security personnel suffered most WPV (42.4%), followed by nurses (32.4%) and doctors (25.4%), which chiefly aligns with previous literature, 12 , 13 suggesting that nurses are more likely to be the victims of WPV than doctors. In this study, security personnel accounted for the largest proportion of victims of WPV, which is at odds with previous sporadic reports where security personnel was being attacked.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that security personnel suffered most WPV (42.4%), followed by nurses (32.4%) and doctors (25.4%), which chiefly aligns with previous literature, 12 , 13 suggesting that nurses are more likely to be the victims of WPV than doctors. In this study, security personnel accounted for the largest proportion of victims of WPV, which is at odds with previous sporadic reports where security personnel was being attacked.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is no workplace or occupational category that does not face this risk ( 4 ). Generally speaking, nurses are more vulnerable to verbal violence than doctors ( 20 ), but doctors are more often victims of physical violence in the workplace ( 21 ). As doctors are the designers and practitioners of medical diagnosis and treatment programs, if patients and their families are dissatisfied with the medical procedures, results or quality, doctors are most likely to be the targets of WPV.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Studies of non-psychiatric healthcare settings reveal that nurses, patient care technicians (PCTs), physicians, and trainees all report increases in verbal and physical abuse, with nurses and PCTs experiencing the highest rates of victimization. 7,[11][12][13] Incivility is an ethical issue It is beyond the scope of this paper to comprehensively analyze the societal underpinnings for this increase in incivility. Popular media hypothesize stress, substance use, and COVID-19 pandemic fatigue as possible factors.…”
Section: Case #2 -Family Member Incivilitymentioning
confidence: 99%
“…Historically, clinicians have commonly disregarded or overlooked their patients' or caregivers' behavior for the sake of professionalism. 15 Many are reluctant to complain, 20 believing that experiencing such behaviors is a rite of passage, 28 that infractions can be handled internally without assistance, 12 or that reporting is voluntary. 29 Moreover, many staff possess limited knowledge of reportable event criteria.…”
Section: Specific Roles That Ethics Committees and Clinical Ethics Co...mentioning
confidence: 99%